UPAYA REHABILITASI EKS PEKERJA SEKS KOMERSIAL (PSK) DI PANTI SOSIAL KARYA WANITA (PSKW) ANDAM DEWI SOLOK - Saefulloh, Ahmad; Nofriza, Nofriza (Palita: Journal of Social Religion Research, 2018)
This study aims to see the rehabilitation efforts of former Sex Workers Commercial (PSK) in Panti Sosial Karya Wanita (PSKW) Andam Dewi Solok. The large number of sex workers becomes a serious problem that must be followed up immediately. The Crowd raids prostitution reported in the media into the spotlight of the world of education in instilling moral education to learners. This is the importance of recognizing the negative impacts. To avoid the proliferation of the practice of prostitution is necessary to preventive and rehabilitative efforts against the perpetrators of prostitution practices that netted raids. This study aims to provide a form of preventive and rehabilitative efforts for the "eks PSK" who were caught raids in social institutions as well as to the general public. This research is a qualitative descriptive study. Data collection by observation method, direct interview and documentation. Techniques used in data analysis are data display, data reduction and conclusion. The data validity technique uses source triangulation. The results showed that: 1) preventive efforts that can be done include the formation of wirid adolescents and regular weekly recitation, 2) submission of grants through grant channeling institutions. While rehabilitative efforts include religious programs, skills and crafts as well as long-term assistance.